Propofol-related urine discoloration in a patient with fatal atypical intracerebral hemorrhage treated with hypothermia - Regensburger, Martin (Springer International Publishing, 2014)
INTRODUCTION: Mild therapeutic hypothermia is an increasingly recognised treatment option to reduce perihemorrhagic edema in severe intracerebral hemorrhage. CASE DESCRIPTION: We report the case of a 77-year old woman with atypical intracerebral hemorrhage that was treated with mild hypothermia in addition to osmotic therapy. The patient’s urine subsequently showed a green discoloration. Urine discoloration was completely reversible upon discontinuation of propofol. DISCUSSION AND EVALUATION: Propofol-related urine discoloration may have been provoked by hypothermia. Due to the benign nature of this side effect, propofol should be stopped and gastrointestinal function should be supported. CONCLUSION: More studies are needed to show a causal role of hypothermia and related decreased enzymatic function.